By definition, the average velocity on the time interval `[t_1,t_2]` is

`(y(t_2)-y(t_1))/(t_2-t_1)` . In this case, we are given that `t_1=4` seconds and `t_2=4+h` seconds. We plug these into the given equation to get

`y(4)=67*4-16*4^2=268-256=12` feet and

`y(4+h)=67(4+h)-16(4+h)^2=268+67h-256-128h-16h^2`

`=-16h^2-61h+12` feet. Now we just plug these into the average velocity formula:

`(y(t_2)-y(t_1))/(t_2-t_1)=((-16h^2-61h+12)-12)/((4+h)-4)`

`=(-16h^2-61h)/h=-16h-61`

The units in the numerator are feet and the units in the denominator are seconds, so the units of velocity turn out to be feet/second, as expected. The reason h can't be 0 is to avoid division by zero.

**The average velocity on the interval [4,4+h] is -16h-61 ft/s.**

` `` `

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.